Dampak Pendidikan Multikultural Pada Madrasah Ibtidaiyah Di Indonesia - Muqarramah Sulaiman Kurdi (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This study delves into implementing multicultural education within Madrasah Ibtidaiyah in Indonesia, employing a library research approach and descriptive analysis methods. The study investigates the influence of multicultural education on curriculum development, challenges, opportunities, and its impact on fostering tolerance and understanding among students. Through an extensive academic literature review, the study unveils multifaceted opportunities, including enhanced cultural understanding, promotion of tolerance, enriched educational experiences, and preparation for global citizenship. However, it also uncovers challenges such as resistance to change, resource constraints, and the need for continuous adaptation. The findings underscore the importance of embracing diversity and fostering inclusive learning environments within religious-based schooling. Overall, this study highlights the potential benefits of multicultural education in Madrasah Ibtidaiyah, emphasizing its role in nurturing culturally competent and globally-aware individuals.